THE ORGANIZATION OF OPERATIONAL CONTROL AND MANAGEMENT OF ROLL FORMING USING SCADA- SYSTEMS - S. A. Teslenko (Литьë и металлургия, 2012)
It is shown that the use Scada-systems for the organization of various systems of automated processes is the most promising method of automation, that gives wide opportunities of control, analysis and management of compiex dynamic, real-time systems.